Penerapan Model Drill and Practice untuk Meningkatkan Kemampuan Berpikir Analitis pada Pembelajaran Matematika - Sri Lestari Indriana Putri; Mohammad Maftukhin; Khoirul Anam; Anik Yunita; Nurul Lailatul Fatimah; Suwindah Suwindah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Analytical thinking ability is one of the important cognitive skills needed by students in solving problems in a systematic and structured manner. One of the learning models that can foster this ability is Drill and Practice. This study aims to describe the steps, advantages, and disadvantages of applying the Drill and Practice model in Mathematics learning at Madrasah Aliyah Negeri 2 Rembang. The research method used a qualitative approach with the subject of Mathematics teachers, while the data collection techniques were interviews, observations, and documentation. The results showed that the steps of Drill and Practice include explaining the purpose of the exercise, initial diagnosis, guided practice, giving short practice time so as not to be boring, reviewing student obstacles, emphasizing the main process, and paying attention to individual differences. With this model, students can improve skills as well as analytical thinking. The advantages of this model include strengthening memory, accelerating skill mastery, instilling disciplined learning habits, making it easier for teachers to control, and training students' agility. However, there are some disadvantages, such as inhibiting student initiative, causing verbalism, making students static, and repetitive exercises can be monotonous and form rigid habits. In conclusion, the Drill and Practice model can be applied to improve analytical thinking skills in learning Mathematics in madrasah.